DEVELOPING COMIC MEDIA ABOUT HUMAN INTERACTION WITH THE ENVIRONMENT TO IMPROVE CRITICAL THINKING SKILLS - Lailatul Fitriah; Maria Veronica Roesminingsih; Suhanadji (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Students' critical thinking has not been maximally trained in learning since learning activities are only memorizing to meet the demands of passing the assessment. Students are less able to understand, build, and criticize arguments about a problem, especially in social studies learning. This study aimed to determine the feasibility of comic media material about human interaction with the environment to improve the critical thinking skills of fifth grade students. This type of research was research and development (Research and Development) with a 4D model. This research was conducted online using Zoom platform, Google Forms, and Ms. Teams that was carried out synchronously and asynchronously due to the Covid-19 pandemic. Data were collected through the expert validation stage and observation sheets, student response questionnaires, and critical thinking tests (pretest and posttest) for the teacher and student activity. Furthermore, the data were analyzed by quantitative and descriptive techniques. The results showed that: (1) comic media was in the very feasible category with a percentage of 82%, (2) it was practical based on teacher activity observations with a percentage of 94% with very active category, 95% for student activity with very active category, and student response questionnaires was 93% with very good category, (3) it was effective based on the result of N-gain on the critical thinking test, which was 0.53 (medium category). Thus, comic media in social studies learning was declared valid, practical, and effective in improving students’ critical thinking skills at fifth grade of elementary school.